Case series: Convalescent plasma therapy for patients with COVID-19 and primary antibody deficiency - Lang-Meli, Julia; Fuchs, Jonas; Mathé, Philipp; Ho, Hsi-en; Kern, Lisa; Jaki, Lena; Rusignuolo, Giuseppe; Mertins, Susanne; Somogyi, Vivien; Neumann-Haefelin, Christoph; Trinkmann, Frederik; Müller, Michael; et al. (Journal of clinical immunology, 2022)
Patients with primary antibody deficiency are at risk for severe and in many cases for prolonged COVID-19. Convalescent plasma treatment of immunocompromised individuals could be an option especially in countries with limited access to monoclonal antibody therapies. While studies in immunocompetent COVID19 patients have demonstrated only a limited benefit, evidence for the safety, timing, and effectiveness of this treatment in antibody-deficient patients is lacking. Here, we describe 16 cases with primary antibody deficiency treated with convalescent plasma in four medical centers. In our cohort, treatment was associated with a reduction in viral load and improvement of clinical symptoms, even when applied over a week after onset of infection. There were no relevant side effects besides a short-term fever reaction in one patient. Longitudinal full-genome sequencing revealed the emergence of mutations in the viral genome, potentially conferring an antibody escape in one patient with persistent viral RNA shedding upon plasma treatment. However, he resolved the infection after a second course of plasma treatment. Thus, our data suggest a therapeutic benefit of convalescent plasma treatment in patients with primary antibody deficiency even months after infection. While it appears to be safe, PCR follow-up for SARS-CoV-2 is advisable and early re-treatment might be considered in patients with persistent viral shedding.
Online veröffentlicht: 10. Dezember 2021
Gesehen am 24.04.2023